Design of wideband antenna using interdigital capacitance - Kannadhasan Suriyan; Kanagaraj Venusamy; Indira Priya Ponnuvel; Syed Khaja Ahmedudin Zakir; Manjunathan Alagarsamy (Institute of Advanced Engineering and Science, 2023)
A pair of wideband antenna serve as an impedance transformer for the proposed antenna, which consists of a dipole with periodic capacitive loading. Periodic capacitive loading is achieved at each sector by adding interlaced coupling lines. In order to create a broad impedance bandwidth, the periodic interlaced coupling lines split each arm of the dipole into five portions. Currents are dispersed on the various sections at different frequencies. The suggested antenna is an excellent choice for radar applications since it has a high gain and a low amount of cross polarisation. With the aid of innovative design methods including codirectional inclusion of interdigital capacitance, this research study proposes an interdigital capacitance for wideband (WB) applications interdigital capacitor (IDC). The suggested IDC antenna, which works between 4.70 and 11 GHz, has dimensions of 6.36x6.35x1.6 mm3. This page explores in-depth data on gain over frequency, far field patterns, and surface current distribution on antennas. The suggested antenna's feasibility is shown by simulation data that demonstrates excellent equality on return loss.